ANALISIS KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN WEBSITE GEPO MENGGUNAKAN METODE PIECES - Nurul Fitrah; Ahyar Muawwal; Marlina (STMIK KHARISMA Makassar, 2022)
Abstract: The Gepo website is a website that contains information on ongoing food and drink promos. So far, 30 users of food and beverage entrepreneurs have joined. The low level of food and beverage entrepreneurs who join is the background to the need for an analysis of customer satisfaction, especially customers of food and beverage entrepreneurs who join the website, which aims to determine the extent of customer satisfaction. In this study, researchers used the PIECES method which has 6 variables to classify problems, namely Performance, Information, Economic, Control, Efficiency and Service. The results of this study are the 6 variables Performance, Information, Economic, Control, Efficiency and Service get the predicate satisfied, but the Information and Performance variables get the lowest average value, and in Performance testing using google tools my site also get bad grades. From the results of this study, it can be seen that the Performance and Information variables must be further improved, and the Economic, Control, Efficiency and Service variables in order to maintain the satisfaction value.